Analysis of cooking shelters in Paulshoek and the effects of harvesting on natural population of Polymita albiflora - Evans, Adrian (Department of Biological Sciences, 2017)
Cooking shelters are found at all the 28 stocking posts in the Paulshoek village. They are round circular structures with walls made from plant materials to provide insulation. Food is prepared and cooked inside the shelters, providing protection from the elements mainly cold and wind. These shelters also serve as social meeting and entertainment venues. Due to the poverty of the area alternatives to constructing cooking shelters are too expensive. Thus the sustainable use of plants used to construct cooking shelters will prevent both species loss and economic expense. There are three types of cooking shelters: full canopy, half canopy and open shelters. 18 shelters including all three types were measured. The volume of plant material calculated and the species composition estimated. The full canopy shelters are generally the largest and well built. These shelters are used in winter and need to be sturdy to withstand the elements and last for a number of years [ 15 years]. Open shelters are less permanent and built more often. As they are not required to be as sturdy a higher proportion of less desirable but more available plant species were used. However in all types the major species used was Polymita albiflora. This species is desirable as a construction material as it packs tightly and the dense foliage supply insulation. Although most shelters were made up of more than one species, only Galenia africana and Euphorbia mauritanica are used consistently in small quantities. Both these species are common and widespread and the amounts being harvested are insufficient to cause any negative effects on the species population dynamics. However P. albiflora is restricted to quartzite slopes or shallow pockets in granite in Northern Namaqualand. Thus harvesting could be destructive to the natural populations. A cooking shelter was dismantled and a size class distribution of P. albiflora used for construction calculated. Transects were run in four separate P. albiflora populations and a size class distribution for all sites calculated. The majority of plants used to build cooking shelters are in the size class 2 0.005-0.015 m³. The size class distribution of natural populations of P. albiflora showed the smallest size class [ <0.005 m³] to have the highest frequency. There was a decrease in the frequency for the remaining size classes. Harvesting from those size classes could cause this reduction. However it is more likely that high mortality during the establishment phase causes this decrease. A regression between volume and number of capsules showed that the plants being removed are not the only reproductively active plants. Small plants [0.001m³] are capable of producing a few capsules each containing more than 100 seeds. Also the few large plants produce up to 300 capsules per plant. P. albiflora is also used as a poor quality fuelwood for baking. Baking occurs approximately once a week. However only populations within the immediate vicinity are threatened by overexploitation due to the efforts required for fetching these plants far outweighs their use as a fuelwoood. This study indicates that P. albiflora is being harvested well within the sustainable limit. P. albiflora grow in dense stand and removal of plants within these will most likely be replaced by small plants or seeds of this species.